Developing a comprehensive structured program for managing gestational diabetes mellitus and preventing type 2 diabetes mellitus in Chinese women: a multi-method study - Huang, Jing; Long, Tianxue; Li, Hua; Cui, Hangyu; Zhang, Dan; Wu, Yi; Zhang, Yiyun; Sun, Xinying; Zhao, Yan; Wei, Yuan; Li, Mingzi (Frontiers in Endocrinology, 2025)
BackgroundGestational diabetes mellitus (GDM) affects pregnancy outcomes and increases the risk of type 2 diabetes mellitus (T2DM) postpartum. Traditional health education interventions have shown positive effects, but adherence to lifestyle management and motivation for continued postpartum care still require improvement. This study aimed to develop a comprehensive structured program for Chinese women with GDM to improve adherence to lifestyle management and motivation for postpartum care, thereby reducing future T2DM risk.MethodsThe development of this program was divided into five steps: (1) Analysis: a summary of evidence and the analysis of needs, population characteristics, teaching content, and teaching environment; (2) Design: the design of learning objectives, teaching logic, and teaching strategies; (3) Development: the creation and development of teaching materials; (4) Implementation: the evaluation of scientific validity and rationality through an expert meeting and trial sessions; (5) Evaluation: formative and summative assessments. Finally, a pilot test was conducted to evaluate its feasibility and acceptability.ResultsLearning objectives were set in the cognitive, affective, and psychomotor domains, with a total of 189 items. The program consisted of five sessions, including: understanding GDM, nutrition and physical activity guidelines, expecting moms—are you ready, postpartum weight management, and reinforcing healthy behaviors. In addition, there was a session specifically for women starting insulin treatment, with the theme: timely insulin injection. Teaching materials included lesson plans, teaching posters, food cards, and a mother’s handbook, etc., totaling 11 items. The pilot study included eight women with GDM, all of whom expressed a positive acceptance of the program.ConclusionsThe feasibility and acceptability of the program were confirmed, and a final version was developed. It features clear objectives, detailed teaching content, engaging teaching materials, and standardized implementation processes, all of which are of significant importance for both short- and long-term management of GDM.